Saving the Holy Sepulchre: how rival Christians came together to rescue their holiest shrine - Cohen, Raymond (Oxford University Press, 2008)
The earthquake -- Mr. Cust's immobile machine -- Ready to fall -- William Harvey's temporary repairs -- Monsignor Testa's temple -- The fire -- Hassan Bey takes charge -- Terrors in the way -- A patriarch open to reason -- Kiss of peace -- Three wise men -- The keys -- To the rotunda -- At last, light -- Trouvelot's choice